A history of women's prisons in England : the myth of prisoner reformation - Menis, Susanna (Cambridge Scholars Publishing, 2020)
This book presents a revisionist prison history which brings to the forefront the relationship between gender and policy. It examines women's prisons in England from the late 18th century to the beginning of the 20th century, drawing attention to the detrimental effect the orthodox closed prison has on penal reform. The text investigates the clash between what was conceptualised as desirable prison policy and the actual implementation and implications of such a penalty on the prisoner. It challenges previous claims made about the invisibility of women prisoners in historical penal policy, and.